Analysis of the paratextual elements of the manual of arithmetic Taboada Curiosa (Portugal, 18th century) - Ripe, Fernando; Maurício Medeiros Alves, Antônio (Universidade Estadual de Campinas, 2021)
This article presents an analysis, under the perspective of the History of Education (and) Mathematics, of the paratextual elements that compose the educational instructions for the teaching of arithmetic present in the pedagogical manual Taboada Curiosa that was written by spanish professor Joam Antonio Garrido. Initially published in 1737 in Lisbon, the work was intended to instruct in the art of counting and writing through the rules that have been applied in the "good Schools" of the Kingdom of Portugal. We consider that Taboada Curiosa was a print of relative editorial success in the context of the seven hundred Portuguese, becoming an efficient pedagogical mechanism for the construction of arithmetic meanings. We will focus our analysis on the peripheral elements that make up the print, especially in the frontispiece, dedication page, the prologue and the summary, highlighting how the arithmetic professor Joam Garrido established discursive strategies of reading directions to his potential consumers of the work.